(untitled) (World Bulletin of Management and Law, 2022)
Much scholarly research has been conducted to investigate the benefits that firms derive from their innovation initiatives. Although some research has found that firm innovativeness is connected with increased export performance, the conditions under which firm innovativeness activities are most and least advantageous remain unknown. Despite the fact that many organizations regard innovation to be their lifeblood, enterprises are frequently challenged to reap the anticipated performance advantages of innovation. The purpose of this research is to investigate the effect of firm innovativeness on firm performance. Through displaying a case study on Kodak Company, the finding of this paper revealed that innovativeness is important factor for the success or failure of the firms. The paper contributes to knowledge that will be of use to managers, researchers, and policymakers.